PARAMETERS THAT AFFECT THE DISSOLUTION OF INDONESIAN GALENA CONCENTRATE IN FLUOROSILICIC ACID AND HYDROGEN PEROXIDE - Rezky Iriansyah Anugrah; M Zaki Mubarok; Dessy Amalia (Indonesian Mining Journal, 2018)
Pyrometallurgical process still dominates the extraction of galena concentrates. The process used to extract the lead includes reduction smelting in a blast furnace, air flash smelting (Boliden process), oxygen flash smelting (Kivcet, Boliden Kaldo, Outokumpu), air-slag bath smelting (Isasmelt) and oxygen-slag bath smelting (QSL). However, those generate dust, SO2 gas and volatile Pb liquid. As a result, such processes are ineffective to treat the complex sulfides and low-grade flotation con concentrates. Referring to the lack of high-grade lead ore the lead pyrometallurgical is a problem in the future. In addition, the environmental regulation becomes very strict lately. Those pushes the metallurgist to seek the alternative process that are environmentally friendly and able to treat the low-grade concentrates. Lead extraction through hydrometallurgical process is considered to be safer as the process do not produce dust, SO2 gas and lead vapor.Researches for lead extraction through hydrometallurgical routes have been performed using various leaching agents such as acetic acid, ferric methanesulfonate, ferric chloride, ferric fluorosilicate and nitric acid with hydrogen peroxide and ferric ion as the oxidants. So far, no lead plant operates hydrometallurgically in an industrial scale. Fluorosilicic acid has a potential to be used as the leaching reagent for concentrating the lead because of high lead solubility in this solution and cheaper price of the reagent in compared to sulfamate and fluoroborate solutions. This research used galena concentrates from a mining area in Bogor, Indonesia, fluorosilicic acid and hydrogen peroxide as the oxidants. The highest Pb extraction percentage of 99.26% was achieved from the leaching experiment using 3.44 M of H2SiF6 and 9.79 M of H2O2, at 97oC and concentrate particle size distribution of -100+150 mesh after 135 minutes. The XRD analysis of the leaching residue with no oxidant showed the presence of galena, sphalerite and chalcopyrite, while the residue of the leaching with oxidant showed anglesite (PbSO4), galena, sphalerite, sulphur and pyrite. Lead extractions were increased by the increase of temperature and concentration of fluorosilicic acid. The best solid percentage that gave the highest lead extraction percentage was 12%. Variations of rotation speeds at the range of 300-700 rpm did not significantly influence lead extraction percentage. However, the particle size distribution that resulted in the best extraction percentage of lead is 100+150#, at which the finer particle size of the concentrate give a lower extraction percentage of the lead due to PbSO4precipitation.